Continuous Improvement Through Kaizen In An Automotive Industry - Prayuda, Rafie Zaidan (Journal of Industrial Engineering & Management Research, 2020)
PT AGP is a company engaged in the automotive industry. In its activities, PT AGP applies the kaizen culture as a corporate culture which includes all activities in the company. The purpose of this study is to describe the process of implementing kaizen culture at PT AGP. This study also illustrates the application of Kaizen by PT AGP related to the implementation of the main concepts of kaizen, the main system of kaizen, and gemba kaizen. The research method used in the study used in this research is descriptive qualitative method. Data collection methods used were interviews with triangulation conducted to 5 participants, direct observation, and documentation. The analytical method used in this study is data reduction, data presentation, and drawing conclusions / verification and data analysis. The results of this study are the application of Kaizen to enrichment to form the mindset of employees related to kaizen. The application of kaizen culture increases the rate of productivity and increases in the perceived benefits of the company. Kaizen activity was introduced as a whole company culture. The application of kaizen activity encourages employee aspirations in improving their performance and contribution to the improvement of the company. 2. The company adopts all components of kaizen culture that have been established by the parent company. Cultural adaptation occurs when employee contributions start to form a kaizen work culture that is more adaptive to reforms that occur in the company. Employee contributions contribute to continuous improvement, improve quality, reduce costs, and shorten delivery time.